Neonatal Alexander Disease: Novel GFAP Mutation and Comparison to Previously Published Cases - Knuutinen, Oula; Kousi, Maria; Suo-Palosaari, Maria; Moilanen, Jukka S.; Tuominen, Hannu; Vainionpää, Leena; Joensuu, Tarja; Anttonen, Anna-Kaisa; Uusimaa, Johanna; Lehesjoki, Anna-Elina; Vieira, Päivi (Neuropediatrics, 2018)
Alexander disease (AxD) is a genetic leukodystrophy caused by GFAP mutations leading to astrocyte dysfunction. Neonatal AxD is a rare phenotype with onset in the first month of life. The proband, belonging to a large pedigree with dominantly inherited benign familial neonatal epilepsy (BFNE), had a phenotype distinct from the rest of the family, with hypotonia and macrocephaly in addition to drug-resistant neonatal seizures. The patient deteriorated and passed away at 6 weeks of age. The pathological and neuroimaging data were consistent with the diagnosis of AxD. Genetic analysis of the proband identified a novel de novo GFAP missense mutation and a KCNQ2 splice site mutation segregating with the BFNE phenotype in the family. The GFAP mutation was located in the coil 2B region of GFAP protein, similar to most neonatal-onset AxD cases with an early death. The clinical and neuroradiological features of the previously published neonatal AxD patients are presented. This study further supports the classification of neonatal-onset AxD as a distinct phenotype based on the age of onset.
Keywords: drug-resistant seizures; hydrocephalus; neuroimaging; leukodystrophy